The experience of neighbourhood in medieval and early modern Europe - Kane, Bronach Christina; Sandall, Simon (Studies in medieval history and culture, 2022)
"The Experience of Neighbourhood in Medieval and Early Modern Europe contributes to nascent debates on concepts of neighbourliness and belonging, exploring the operation of the pre-modern neighbourhood in social practice. Formal administrative units, such as the manor and the parish, have been the object of much scholarly attention yet the experience and limits of neighbourhood remain understudied. Building on recent advances in the histories of emotions and material culture, this volume explores a variety of themes on residential proximity, from its social, cultural and religious implications to material and economic perspectives. Contributors also investigate the linguistic categories attached to neighbours and neighbourhood, tracing their meaning and use in a variety of settings to understand the ways that language conditioned the relationships it described. Together they contribute to a more socially and experientially grounded understanding of neighbourly experience in pre-modern Europe"--
Keywords: naapuruus; naapurit; kaupungit; kaupunkisosiologia; historia; Neighborhoods : Europe : History; Neighborliness : Europe : History; Cities and towns : Europe : History; Sociology, Urban : Europe : History; Eurooppa; Europe : Social conditions